Effect of Temperature of the Sensitization Process on the Passive Hemagglutination Test for Hepatitis B Antibody - Hawkes, Royle A. (1973)
The temperature at which the coupling of antigen to erythrocytes takes place is an important factor in the passive hemagglutination test for hepatitis B antibody. Erythrocytes sensitized at 16 C are much less sensitive for the detection of antibody than are those sensitized at 22 to 41 C.